Occasional cooperative breeding in birds and the robustness of comparative analyses concerning the evolution of cooperative breeding. Issue 1 (December 2016) - Griesser, Michael; Suzuki, Toshitaka
Abstract Cooperative breeding is a widespread and intense form of cooperation, in which individuals help raise offspring that are not their own. This behaviour is particularly well studied in birds, using both long-term and comparative studies that have provided insights into the evolution of reproductive altruism. In most cooperatively breeding species, helpers are offspring that remain with their parents beyond independency and help in the raising of younger siblings. However, many cooperatively breeding species are poorly studied, and in 152 species, this behaviour only has been observed infrequently (i.e., occasional cooperative breeding). Here we argue that the parental care mode of these 152 species needs to be treated with caution, as factors associated with occasional cooperative breeding may differ from those associated with "regular" cooperative breeding. In most cooperatively breeding species, helpers provide alloparental care at the nests of their parents or close relatives; however, only in one occasionally cooperatively breeding species do offspring remain into the next breeding season with their parents. Accordingly, different factors are likely to be associated with regular and occasional cooperative breeding. The latter behaviour resembles interspecific feeding (i.e., individuals feed offspring of another species), which occurs when birds lose their brood and begin feeding at a nearby nest, or when birds mistakenly feed at another nest. Thus, we advise researchers to exclude occasional cooperative breeders in comparative analyses until their status is clarified, or to categorize them separately or according to the typically observed parental care mode. This approach will increase the robustness of comparative analyses and thereby improve our understanding of factors that drive the evolution of cooperative breeding.